SoftALPPS - A novel, individual procedure for patients with advanced liver tumors. Issue 8 (August 2022) - Steffani, Marcella; Stöss, Christian; Laschinger, Melanie; Assfalg, Volker; Schulze, Sarah; Mogler, Carolin; Lohöfer, Fabian; Paprottka, Philipp; Hüser, Norbert; Friess, Helmut; Hartmann, Daniel; Novotny, Alexander
Abstract: Background: The first-line therapy for liver malignancies is a radical extended liver resection. This high-risk operation has a high incidence of post-hepatectomy liver failure (PHLF) due to a small future liver remnant (FLR). One of the procedures to increase the FLR is the associating liver partition and portal vein ligation for staged hepatectomy (ALPPS) which is still associated with high morbidity and mortality. Here, we present a new, less invasive ALPPS variant that may be associated with lower morbidity. Methods: Soft ALPPS is characterized by reduced trauma to the liver tissue and individual adaptation to the patient's health constitution. In soft ALPPS, portal vein embolization (PVE) is performed instead of portal vein ligation (PVL) after complete recovery of liver function. In addition, a non-absorbable foil was avoided in order to be able to extend the interval to step two or skip step two when required. Results: Four patients successfully underwent soft ALPPS. Two of these patients have been followed-up for over a year (one patient with Klatskin tumor, one patient with extensive HCC). Both patients show no evidence of recurrence after 12 months and are in good medical condition. The other two patients who recently had surgery are also doing well. Conclusion: Soft ALPPS offers the chance to curatively resect patients with high tumor burden of the liver even when the FLR is inadequate. This individual therapy method can give patients the possibility of complete tumor resection and can help to reduce perioperative morbidity.